1995
DOI: 10.1089/jir.1995.15.243
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Inhibitor of Interleukin-lβ Converting Enzyme Prevents Endotoxin-Induced Interleukin-lβ ProductionIn VitroandIn Vivo

Abstract: A potent, reversible, tetrapeptide inhibitor of interleukin-1 beta converting enzyme (ICE), L-709,049, has been shown to suppress the in vitro production of mature IL-1 beta. We now report that this inhibitor also effectively suppresses the production of mature IL-1 beta in a murine model of endotoxic shock. Intraperitoneal administration of L-709,049 reduced the elevations of IL-1 beta in the plasma and peritoneal fluid of mice treated with LPS in a dose-related manner (ED50 = 2 +/- 0.9 mg/kg). LPS-induced el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 12 publications
2
18
0
Order By: Relevance
“…22,23 In contrast, no beneficial effects on LV myocyte structures and functions were observed when serum obtained from endotoxin-and zVAD.fmk-treated rats was used. This is consistent with either high cell permeability and serum short half-life 24,25 or absence of effects on immune response of small peptide caspase inhibitors. Caspase-3-like activation can be directly responsible for septic serum-induced cardiomyocyte contractile dysfunction.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…22,23 In contrast, no beneficial effects on LV myocyte structures and functions were observed when serum obtained from endotoxin-and zVAD.fmk-treated rats was used. This is consistent with either high cell permeability and serum short half-life 24,25 or absence of effects on immune response of small peptide caspase inhibitors. Caspase-3-like activation can be directly responsible for septic serum-induced cardiomyocyte contractile dysfunction.…”
Section: Discussionsupporting
confidence: 82%
“…Cell viability (trypan blue exclusion) and nuclear condensation (Hoechst 33342 staining, 1 g/mL) of LV cardiomyocytes isolated from control and endotoxin-treated rats were quantified over time. Cell viability in control and septic LV cardiomyocytes remained up to 80% over time (4,24, and 96 hours; data not shown). Few condensed nuclei (Hoechst staining) were detected (Ͻ5%) in control and septic LV cardiomyocytes at 4 and 24 hours after isolation (data not shown).…”
Section: Endotoxin Rat Treatment Induces Cardiomyocyte Caspase Activamentioning
confidence: 88%
“…However, the importance of TACE as a pivotal enzyme in the development of inflammatory responses is indisputable given the ability of TACE inhibitors to dramatically reduce circulating TNF␣ levels in endotoxin-treated rats and mice (1-3). The importance of ICE in inflammation is also well documented in studies reporting successful amelioration of inflammation in various animal models by inactivation of this enzyme, e.g., ICE inhibitors reduced systemic inflammation induced by endotoxin in mice (41) and ICE-deficient mice were resistant to endotoxic shock (42). In contrast, it was found that localized inflammation induced by turpentine application to the skin induced levels of the IL-1␤-dependent cytokine, IL-6, in ICE-deficient mice that were comparable to those of wild-type mice, whereas no IL-6 was produced in IL-1␤-deficient mice (16).…”
Section: Discussionmentioning
confidence: 91%
“…Serum IL-18 levels were dependent upon the LPS dose, which is depicted on the upper x-axis so that IL-18 levels correlate with the corresponding stimulating dose of LPS. known to protect animals from lethal inflammation (11,41,42). In addition, the cas-1-inducing activity (Figs.…”
Section: Il-18 Levels and Cas-1 Activity Are Interdependentmentioning
confidence: 99%